Shop less, think more : consumers' engagement in slow fashion - Pinto, Inês Maria Rosete (2019)
The Slow Fashion movement has been gaining momentum due to the increasing desire to mitigate the harmful impact of the fashion industry and raise awareness of sustainability issues into society. The novelty of the topic has led previous authors to focus on the definition of ‘Slow Fashion’. However, a limited number of studies were conducted about the actual consumers. The present dissertation aims to understand consumers’ behavior towards Slow Fashion namely motivations and barriers to engage in the topic. Hence, a netnographic approach is taken to map consumers’ expressions and thoughts of Slow Fashion in an online environment. Results show that the movement generates different feelings and opinions among consumers comprising the themes of Accountability, Fascination and Complexity. On one side, there is an expressed desire not to contribute for the actual fashion system and increase awareness of the Slow Fashion topic by sharing practices. There is also a fascination towards the process of learning and discovery of the topic that allows for an emotional connection with personal garments. Contrary, the complexity of the subject is hindering Slow Fashion engagement. The mistrust in brands, governments and technology along with the existent controversies about the topic imped the adoption of Slow Fashion movement on a mainstream level. Therefore, reinforcing transparency and clear communication between providers and consumers is imperative to increase consumers’ confidence in their choices. Implications also include the development of business models aligned with the new generations’ values and necessities.